USULAN RUTE DISTRIBUSI MENGGUNAKAN ALGORITMA SWEEP DAN LOCAL SEARCH (STUDI KASUS DI PERUSAHAAN X) - Muhamad Ruben; Arif Imran (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
A company has to deliver its product to thirty-five points/customers. In delivering process, there are limitations such as the number of vehicles, vehicle capacity, and driver's working hours. The company wants to find a better/shorter route in distributing its product to customer in order to minimize the transportation cost. The problem can considered as the Capacited Vehicle Routing Problem. In this paper, the Sweep algorithm are first used to find the initial solution. The local search procedures are used to the solution obtained by the Sweep algorithm. Four local searches are applied, 1-insertion intra-route, 1- insertion inter-route, 1-1 intra –route and 1-1 inter-route. The solutions produced by each local search are then compared, and the best one is selected. The best solution is given by the 1-Insertion intra-route procedure. It is 27,923 km shorter (15% better) than the current routes.